Comparison of methods for stable isotope ratio (δ13C, δ15N, δ2H, δ18O) measurements of feathers. Issue 4 (20th March 2014) - Bontempo, Luana; Ceppa, Florencia; Ziller, Luca; Pedrini, Paolo; Hobson, Keith A.; Wassenaar, Leonard I.; Camin, Federica; Davey, Matthew
Summary Natural variations in the stable isotope ratios of bioelements in bird feathers are being increasingly used by animal ecologists to investigate different aspects of bird life. However, to ensure reliability of the data, a critical and very delicate aspect is the preparatory phase (cleaning, drying and subsampling) and the proper analysis, mainly in relation to δ2H and δ18O, respectively, for the presence of exchangeable Hs and of nitrogen and sulphur in keratin. With respect to determination of the isotope ratios of C, N, O and H, in this work, we compare the cleaning mixture most commonly used in the literature (chloroform : methanol 2 : 1) with diethylether : methanol 2 : 1, which avoids the use of the carcinogenic solvent chloroform. We also compared oven‐drying with air‐drying of samples, as well as subsampling of feathers by cutting with surgical scissors or cryogenic pulverization. Finally, we investigated whether stable isotope ratios varied along the vane and between the rachis and vane. The different methods compared in the three preparatory stages showed no differences performance‐wise and can therefore be used interchangeably. Variability in stable isotope ratios can be considerable, both along the vane and between rachis and vane, which is because their compositions register changes in diet, area and climate. However, in this specific study, when the parts of the feather closest to the calamus were removed, the delta values were clearly more homogeneous. Finally, we demonstrate that a casein with a known δ2H value, although probably differing from keratin in the number of exchangeable Hs, can be used to normalize the δ2H values of feathers, although only in the range of values close to that of the reference material. In determining δ18O, the use of a longer gas chromatography‐GC column, its frequent change and the use of a linear equation built with matrix match equivalent reference materials seems to reduce the drift of GC column performance due to the presence of nitrogen and the accumulation of sulphur.